Immunohistological localisation of Coxiella burnetii in various organs of naturally Q-fever infected goats - Lukman, Norina; Yusoff, Md. Sabri; Goh, Yong Meng; Saad, Mohd Zamri; Awang Besar, Sarenasulastri; Mohd Hanan, Latifah; Jaadil, Jamilah; Mohamed Mustapha, Noordin (Universiti Putra Malaysia Press, 2011)
The rather uncommonly reported Q-fever disease in Malaysia is currently demonstrating an increasing trend of outbreaks. A total of 197 goat carcasses during the period of July 2007 to December 2009 were submitted to Regional Diagnostic Laboratory (MVK), Bukit Tengah, Penang, for post-mortem examination. Morphological diagnosis of necrotic placentitis, interstitial pneumonia, hepatitis and nephritis were observed in majority of the cases. Likewise, Giemsa stained sections of selected tissues revealed C.burnetii trophoblast. Acute cases yielded lesions conforming to doughnut granuloma, while those of the chronic form exhibited chronic inflammation. In an attempt to further confirm the presence of the organism, these selected tissues were subjected to immunohistochemical confirmation. Out of the total suspected cases, 152 (77.2%) were confirmed as positive of Q-fever based on their IHC. Thus, this study demonstrated pertinent lesions of acute and chronic forms of Q-fever which might be beneficial to laboratories without IHC facilities.